Strategies for Living in Houses - Colin Ripley (Footprint)
The problem of queer housing can never go away because it is a central component of queerness. Queer housing is a contradiction in terms: not even a queer architect can design a queer house. But where does this leave us, as queer people living in a straight hegemony? Where does it leave us as humans with bodies, craving shelter and safety and a place to live that is in accordance with our experience of self and of living in the world? In this article the author proposes eight architectural strategies for re-occupying the Levittown Cape Cod house from 1947 for queer bodies, minds and hearts. These strategies offer modes by which the key programmatic formal and material components of the Cape Cod House can be attacked, made invalid, or détourned for queer uses, to make of the Cape Cod House a site for our pain, our longing, our anger.